FINANCIAL POLICY STRATEGY IN INCREASING ECONOMIC VALUE ADDED ON MSMES IN MEDAN CITY - Sugiharto, Sugiharto; Tripure Maas, Linda; Sadalia, Isfenti; Sinta, Irada (CV. Radja Publika, 2021)
The global Covid-19 pandemic certainly has an impact on various sectors, especially in the economic sector and of course also has a significant impact on tourism, the trade sector, industry including Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Creative products have great potential to be able to deliver the city that has the industry into an advanced and independent creative economy city. The use of information technology for business resource management for creative products is still under-attentioned, which in turn has administrative, financial, process, and access to banking and financial institutions weaknesses. This study aims to formulate a strategy to increase added value for the MSME sector of North Sumatra Province, namely the Economic Value-Added method and implement efforts to cooperate with the Indonesia Stock Exchange through the mechanism of acceleration boards and Initial Public Offering (IPO) to obtain long-term financing facilities and introduce MSME business unit to the wider community into a medium-class public company. This scientific research also aims to provide recommendations for sustainable strategies for the MSME sector, especially in the province of North Sumatra in running a business amidst the Covid-19 pandemic. This type of research is qualitative research using a mix method by conducting interviews with the target population, namely 200 Micro, Small and Medium Enterprises spread in North Sumatra Province and formulating a model for increasing MSME productivity with the introduction of the acceleration board method and collaborating with the Indonesia Stock Exchange in the coaching process. In this study, a focus group discussion will be held by inviting local officials from related offices of North Sumatra province and academics to provide input in completing the strategy development model for increasing MSME productivity by focusing on the Economic value-added method. The outputs of this research are publications of reputable international journals, international proceedings, and reference books for ISBN certified research results with TKT level 3.